Techno-economic and life cycle environmental assessments of CO2 utilization for value-added precipitated calcium carbonate and ammonium sulfate fertilizer co-production - Feyza Kazanç; Peng Zhang; Partha Saha; Yongqi Lu (Journal of CO2 Utilization)
An advanced CO2 mineralization technology using Flue Gas Desulfurization (FGD) byproduct gypsum, which coproduces value-added precipitated calcium carbonate (precipitated CaCO3, PCC) and ammonium sulfate [(NH4)2SO4, AS] fertilizer, is being developed to address the technical challenges of achieving simultaneous CO2 capture and utilization, high CO2 and calcium conversion, and enhanced energy efficiency. This study aimed to conduct a techno-economic analysis (TEA) and a life cycle assessment (LCA) for this technology. In the TEA, mass and energy balances for CO2 mineralization integrated with a power plant to utilize all FGD gypsum and approximately 51,000 tonne/year of CO2 in flue gas were developed through modeling. Major equipment was selected and sized, followed by capital and operating cost analyses. Energy efficiency was improved through the integrated use of both low-grade steam and vacuum from the power plant steam cycle. TEA results revealed that this process was profitable, with a levelized net profit of $328.4 per tonne of CO2 utilized. The LCA was performed as a cradle-to-gate study for comparative assessments of global warming potential (GWP) and other environmental impacts between the CO2 mineralization system (i.e., Proposed Production System or PPS) and the conventional processes (i.e., Comparison Production System or CPS). The PPS resulted in a GWP impact of 0.85 kg CO2-Eq per 1 kg of primary PCC production and 1.32 kg of byproduct AS production, approximately 64 % lower than that of the CPS. The LCA results for other environmental impacts also consistently showed impacts 35–88 % lower for the PPS compared to the CPS.